Relative Advantages Of F, Hybrids And 50:50 Physical Mixture In Tomato - Sheela AG (Department of Olericulture, College of Horticulture, 1986)
Bacterial wilt caused by Pseudomonas solanacearum E.F. Smith is the most serious disease limiting the successful cultivation of tomato (Lycopersicon esculentum Mill.) in the acidic soils of Kerala. Development of F1 hybrids possessing different resistant gene systems would be a desirable step in tomato improvement. Development of specific physical mixtures could also minimise crop damage considering the ‘Obstruction’ given by the component lines. Experiments were carried out during 1984-’85, at the Instructional Farm of College of Horticulture, Vellanikkara, Trichur to identify new sources of resistance to bacterial wilt. The susceptible check Pusa Ruby showed 100% susceptibility in all the trials. Six specific tomato lines-LE 79 LFE, LE 214, LE 217, IIHR Bwr 93, IIHR Bwr 34A and LE 206-were crossed in all possible combinations. All F1 hybrids except IIHR Bwr 93 x IIHR Bwr 34A and IIHR Bwr 34A x LE 206 were resistant to bacterial wilt. LE 214 x LE 206 were resistant to bacterial wilt. LE 214 x LE 206 (921.75 g/plant), the best F1 hybrid, had 27.15 fruit/plant and was earlier to fruit set (57.8 days) and fruit harvest (85 days). Among the 15 physical mixtures, six were resistant-LE 214 + LE 217 (16.67%), LE 214 + IIHR Bwr 93 (18.33%), LE 214 + IIHR Bwr 34A (10%), LE 217 + IIHR Bwr 34A (13.33%). LE 214 + IIHR Bwr 93, the best resistant physical mixture, had 24 fruits/plant weighting 600.38 g/plant. Intervarietal heterosis was observed for plant height, primary branches/plant, days to fruits/plant and fruit yield/plant. Combining ability analysis indicated the role of both additive and non-additive geneaction in the expression of days to fruit set, days to fruit harvest, and plant height. Additive gene action was predominant for primary branches/plant. A preponderance of non-additive gene action over additive gene action was observed for fruit/plant and fruit yield/plant. To study the maternal parental effect, five lines of tomato- LE 79 LFF, LE 214, LE 217, IIHR Bwr 93 and LE 206- were crossed in all possible combinations including reciprocals. Maternal parental effect was pronounced for days to fruit set, days to fruit harvest and fruit set (%). Evaluation of 15 reportedly resistant lines of tomato confirmed resistance in LE 211, LE 214, LE 217, LE 79 LFG and LE 79 DG. The line LE 79 LFG was the highest yield (742.6 g/plant) with 19.67 fruits/plant.